Designing for interaction : creating smart applications and clever devices. - Saffer, Dan, ....- (Berkeley : New Riders, 2007)
Designing for Interaction is an introductory book to the practice of interaction design, the new design discipline that is behind such products as the iPod and innovative Web sites like Flickr. Aimed at new practitioners and students, as well as user experience professionals and developers, it is comprehensive look at the discipline, from its history to current methods to its future. While other books on this subject are either aimed at more seasoned practitioners or else are too focused on a particular medium like software, this guide will take a more holistic approach to the discipline, looking at interaction design for the Web, software, and devices. It is also the only interaction design book that is coming from a design background, not a computer science one. This much-needed guide is more than just a how-to manual. It covers interaction design fundamentals, approaches to designing, design research, and more, and spans all mediums--Internet, software, and devices. Even robots! Filled with tips, real-world projects, and interviews, you'll get a solid grounding in everything you need to successfully tackle interaction design.
Keywords: Software-ergonomie.